2014
DOI: 10.3109/03602532.2014.924962
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation and bioactivation reactions of alicyclic amines in drug molecules

Abstract: Aliphatic nitrogen heterocycles such as piperazine, piperidine, pyrrolidine, morpholine, aziridine, azetidine, and azepane are well known building blocks in drug design and important core structures in approved drug therapies. These core units have been targets for metabolic attack by P450s and other drug metabolizing enzymes such as aldehyde oxidase and monoamine oxidase (MAOs). The electron rich nitrogen and/or α-carbons are often major sites of metabolism of alicyclic amines. The most common biotransformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 142 publications
2
38
0
Order By: Relevance
“…This spectrum of metabolites has been confirmed in vivo in man by the results of this trial. These metabolites are in line with the established biotransformation products of a morpholine moiety in several other compounds, describing formation of lactam and lactone metabolites as the predominant pathways, with further degradation of the ring structure by oxidation [13]. The removal of the morpholine ring structure, as observed for the formation of metabolite M2, is well-established for mammalian biotransformation of related alkylmorpholine-structures [14, 15], although sometimes without the extensive oxidation of the remaining alkoxy-chain observed for copanlisib, leading to M2 and finally resulting in M4.…”
Section: Discussionsupporting
confidence: 58%
“…This spectrum of metabolites has been confirmed in vivo in man by the results of this trial. These metabolites are in line with the established biotransformation products of a morpholine moiety in several other compounds, describing formation of lactam and lactone metabolites as the predominant pathways, with further degradation of the ring structure by oxidation [13]. The removal of the morpholine ring structure, as observed for the formation of metabolite M2, is well-established for mammalian biotransformation of related alkylmorpholine-structures [14, 15], although sometimes without the extensive oxidation of the remaining alkoxy-chain observed for copanlisib, leading to M2 and finally resulting in M4.…”
Section: Discussionsupporting
confidence: 58%
“…Thirteen recombinant UGT enzymes (at 0.125 mg/ml) were assessed for their ability to form 3-hydroxydesloratadine when supplemented with recombinant CYP2C8 (25 pmol/ml) and 1 mM NADPH with 10 mM UDP-GlcUA, followed by a 2-hour incubation with 1 or 10 mM desloratadine. and humans, the two species whose hepatocytes catalyzed the highest rate of formation of 3-hydroxydesloratadine (Kato et al, 2013;Bolleddula et al, 2014). It was previously reported that rabbits may be a particularly useful species for nonclinical studies of drugs that undergo N-glucuronidation in humans (Chiu and Huskey, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although bioactivation of the morpholine ring is uncommon and generally considered undesirable (Bolleddula et al, 2014), formation of the pharmacologically active M21 metabolite contributed to the JAK1/2 and ACVR1 inhibitory effect of MMB observed in humans. A similar improvement in efficacy via bioactivation of the morpholine ring has been reported with the anticancer drug methoxymorpholinyl doxorubicin (a doxorubicin analog), but AOX was not involved (Bolleddula et al, 2014). Further, the metabolism of crizotinib on the piperidine ring leads to the formation of its active, major circulating metabolite crizotinib lactam without AOX involvement (Johnson et al, 2015).…”
Section: Pharmacokinetics and Disposition Of Momelotinibmentioning
confidence: 99%
“…In the case of MMB, however, bioactivation of the morpholine ring at the a-carbon next to nitrogen with nitrogen directly attached to phenyl via P450 followed by AOX appears to be a unique occurrence. Metabolism of the morpholine ring in drugs such as linezolid, gefitinib, and methoxymorpholinyl doxorubicin typically occurs via the P450 system (Lau et al, 1989;Wynalda et al, 2000;Quintieri et al, 2005;Bolleddula et al, 2014).…”
Section: Pharmacokinetics and Disposition Of Momelotinibmentioning
confidence: 99%